Kritik Terhadap Quantum Learning dan Quantum Teaching - Armia Armia; Syahbudin Gade; Teuku Alamsyah (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This study aims to reveal criticisms or input on the quantum teaching and quantum learning learning models. This study uses the Content Analysis method. The data sources for this research are articles that have been published on the topic of quantum teaching and quantum learning, the Qur'an and various other sources. In applying the learning model, the following matters must be considered; (1) managing the implementation of learning, (2) the communication process in applying the model, (3) learning plans that will be applied to students. (4) student activities, (5) student learning outcomes. In addition, to apply a learning model also needs to be considered; (1) the character of the students, (2) the basic abilities of the students, (3) the availability of facilities and infrastructure, time allocation, (4) the ability of the teacher, (5) the results to be achieved. The results of this study indicate that the quantum learning model has several advantages and disadvantages. Criticism of the quantum teaching and quantum learning learning models based on the considerations above, criticism of the quantum teaching and quantum learning learning models are; (1) requires careful preparation for teachers and a supportive environment; (2) takes a long time to implement, (3) requires and demands more specific teacher expertise and skills. (4) It is difficult to understand the different characters of students, (5) it is difficult to identify children's skills, (6) it requires large finances and each child has different abilities. The criticisms mentioned above are intended so that in order to apply the learning model, it is necessary to consider these various criticisms so that the teaching-learning process is truly useful and runs well.